2022
DOI: 10.1021/acsapm.2c00863
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Nonwoven Nanofiber Membranes as Nanostructured Supports for Enzyme Immobilization

Abstract: The high porosity, interconnected pore structure, and high surface area-to-volume ratio make the hydrophilic nonwoven nanofiber membranes (NV-NF-Ms) promising nanostructured supports for enzyme immobilization in different biotechnological applications. In this work, NV-NF-Ms with excellent mechanical and chemical properties were designed and fabricated by electrospinning in one step without using additives or complicated crosslinking processes after electrospinning. To do so, two types of ultrahigh-molecular-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Moreover, yields of 96 % to DFF (2,5‐diformylfuran) were obtained with the co‐immobilized enzymes, much higher than the 53 % obtained with soluble enzymes without co‐immobilization. In the study of Medina‐Castillo et al., [26] the immobilization yields were moderate (40–70 %) by both covalent attachment and ionic adsorption; however, the effectiveness factors were significantly low (1‐10 %), showing the difficulty of successfully immobilizing this enzyme on activated carriers.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, yields of 96 % to DFF (2,5‐diformylfuran) were obtained with the co‐immobilized enzymes, much higher than the 53 % obtained with soluble enzymes without co‐immobilization. In the study of Medina‐Castillo et al., [26] the immobilization yields were moderate (40–70 %) by both covalent attachment and ionic adsorption; however, the effectiveness factors were significantly low (1‐10 %), showing the difficulty of successfully immobilizing this enzyme on activated carriers.…”
Section: Resultsmentioning
confidence: 95%
“…The specific technical features of the support materials used in this study can be found in the Supporting Information (Table S1). To achieve an effective immobilization of GalOx, we explored different strategies based on previous successful immobilization procedures [26] . The first strategy we tested was covalent bonding via glyoxyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the hydroxyl groups of cellulose were functionalized with vinyl sulfone groups to obtain Cellu-VS. To do so, a piece of cellulose (16 × 11 cm) was introduced into 70 mL of a solution of DVS (0.33 M) in sodium carbonate buffer (333 mM) at pH = 12.00 for 2 h. Subsequently, Cellu-VS was washed three times with distilled water for 15 min and dried at 50 °C in a vacuum oven. It is well-known that vinyl sulfone groups can react easily with amine groups in mild conditions by a Michael-type reaction [ 26 ]. Thus, in a second step, Cellu-VS (16 × 11 cm) was introduced into 70 mL of a solution of ethylene diamine (0.33 M) in phosphate buffer (100 mM) at pH = 8 for 4 h. Then, Cellu-NH 2 was washed three times with distilled water and dried at 50 °C in a vacuum oven.…”
Section: Methodsmentioning
confidence: 99%
“…Nanostructured supports are materials containing nanometer size features (normally, between 1 and 100 nm), such as nanoparticles (NPs) of different sizes and shapes including nanorods and nanofibers, materials with pores in a nanometer range, stimuli responsive nano-carriers, etc. [ 11 , 12 , 13 , 14 , 15 , 16 ]. This growing interest is explained by a possibility of nanobiocatalysts to overcome deficiencies of enzymes immobilized on traditional supports.…”
Section: Introductionmentioning
confidence: 99%